A Multifaceted Presentation of Xerophthalmia in Autistic Patients - Anuar Zaki Azmi; Sylves Patrick; Mohamad Israk Isa; Shuaibah Ab Ghani (Cureus, Inc., 2023)
We report the manifestations of vitamin A deficiency (VAD) in three children with underlying autism of different stages. These children were under developmental paediatrician follow-up for autism, and the VAD was not detected until these children presented to Ophthalmology screening for varying stages of signs and symptoms. On further assessment, all of our patients have VAD secondary to poor dietary intake, as autistic patients are associated with having selective eating habits. In our case series, we discuss the spectrum of xerophthalmia presentations, which can be mild and can manifest as punctate epithelial erosions to the more blinding complications at the advanced stage of the disease, mainly irreversible optic neuropathy. The primary management is to address the dietary routine coupled with systemic administration of vitamin A.